β-Adrenoceptor-mediated Relaxation of Urinary Bladder Muscle in β2-Adrenoceptor Knockout Mice - Propping, Stefan; Lorenz, Kristina; Michel, Martin C.; Wirth, Manfred P.; Ravens, Ursula (Frontiers in Pharmacology, 2016)
Background and Objective. In order to characterize the β-adrenoceptor (AR) subtypes involved in agonist-stimulated relaxation of murine urinary bladder we studied the effects of (-)-isoprenaline and CL 316,243 on tonic contraction and spontaneous contractions in detrusor strips of wild-type (WT) and β2-AR knockout (β2-AR KO) mice. Materials and Methods. Urinary bladders were isolated from male WT and β2-AR KO mice. β-AR subtype expression was determined with quantitative real-time PCR. Intact muscle strips pre-contracted with KCl (40 mM) were exposed to cumulatively increasing concentrations of (-)-isoprenaline or β3-AR agonist CL 316,243 in the presence and absence of the subtype-selective β-AR blockers CGP 20712A (β1-ARs), ICI 118,551 (β2-ARs) and L748,337 (β3-ARs). Results. Quantitative real-time PCR confirmed lack of β2-AR expression in bladder tissue from β2-AR KO mice. In isolated detrusor strips, pre-contraction with KCl increased basal tone and enhanced spontaneous activity significantly more in β2-AR KO than in WT. (-)-Isoprenaline relaxed tonic tension and attenuated spontaneous activity with similar potency, but the concentrations required were two orders of magnitude higher in β2-AR KO than WT. The concentration-response curves (CRC) for relaxation were not affected by CGP 20712A (300 nM), but were shifted to the right by ICI 118,551 (50 nM) and L748,337 (10 µM). The -logEC50 values for (-)-isoprenaline in WT and β2-AR KO tissue were 7.98 and 6.00, respectively, suggesting a large receptor reserve of β2-AR. (-)-CL 316,243 relaxed detrusor and attenuated spontaneous contractions from WT and β2-AR KO mice with a potency corresponding to the drug’s affinity for β3-AR. L743,337 shifted the CRCs to the right. Conclusion. Our findings in β2-AR KO mice suggest that there is a large receptor reserve for β2-AR in WT mice so that this β-adrenoceptor subtype will mediate relaxation of tone and attenuation of spontaneous activity under physiological conditions. Nevertheless, upon removal of this reserve, β3-AR can also mediate murine detrusor relaxation.